A survey of the sanitary quality of the La Loma Lechon - Victoria, Yvonne R.; Acevedo, Teresita P. (1976)
Samples from four lechon dealers in La Loma were evaluated for sanitary quality. The indices used were the coliform count, using average plate count on brilliant green bile agar; Salmonella count, using the MPN technique and; coagulase positive Staphylococcus enumeration, by plating on S.M. no. 110 agar an conducting biochemical tests. Generally, the experiment revealed that the La Loma lechon is fit for consumption and does not carry a significant number of food poisoning and food infecting microorganisms. However, organisms indicative of dust and fecal contamination were isolated. Coliforms in the pork skin and meat of the samples ranged from 2.3x10^4 to 9.2x10^5 per gram, indicating the necessity of improvements in the hygienic condition of the personnel and the area in general.
Includes bibliographies and appendices.
Thesis (B.S.)--University of the Philippines Diliman
Typescript.
Keywords: Roasting (Cookery); Cookery (Pork); Food handling